A Juridical Analysis of Patient Health Data Protection in Digital Systems - X.Limanto; Y.Mulyadi (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: The rapid digitization of healthcare systems has revolutionized patient data management, but it simultaneously introduces profound vulnerabilities regarding data privacy and security. This study addresses the legal complexities surrounding the protection of electronic health records (EHRs) within digital health ecosystems. Methods: Utilizing a normative juridical research method, this study analyzes existing statutory frameworks, international legal instruments, and theoretical legal principles governing data protection. Results: The analysis reveals that while current frameworks provide foundational protections, severe normative gaps persist regarding unauthorized third-party access, lack of explicit institutional liability, and ambiguous enforcement mechanisms during cross-border data transmissions. Discussion: The discussion integrates an extensive literature review, examining the intersection of privacy rights and digital healthcare infrastructure. It highlights the tension between public health utility and individual confidentiality, demonstrating how decentralized systems and cloud computing exacerbate statutory vulnerabilities. The legal landscape requires a harmonized approach that clearly defines the liabilities of healthcare providers and digital platform operators, ensuring that technological advancements do not outpace fundamental privacy rights. Conclusions: This study concludes that current legislative structures are insufficiently equipped to manage the sophisticated nature of modern cyber threats and digital data handling in healthcare. To bridge these gaps, it is imperative to enact comprehensive legislative amendments, establish a dedicated regulatory oversight body, and implement stringent technological standards such as end-to-end encryption and mandatory breach notifications.